Antecedents and correlates of visual field deficits in children born extremely preterm. (January 2015) - Holm, Mari; Msall, Michael E.; Skranes, Jon; Dammann, Olaf; Allred, Elizabeth; Leviton, Alan
Abstract Aim We sought to identify the antecedents and correlates of visual field deficits (VFDs) at age 2 years among infants born before the 28th week of gestation. Methods The visual fields of 1023 infants were assessed by confrontation at age 2 years. We compared the ante-and postnatal characteristics and exposures of the 65 infants with a VFD to their peers who did not have a VFD. We used time-oriented logistic regression risk models to assess the associations of potential antecedents and correlates with a VFD. Results In the final regression model, VFD was associated with maternal consumption of aspirin during the current pregnancy, recurring/persistent acidemia during the first 3 postnatal days, cerebral ventriculomegaly seen on neonatal ultrasound, prethreshold retinopathy of prematurity (ROP), and supplemental oxygen and ventilator dependence at 36 weeks post-menstrual age. Birth before the 27th week was also associated with increased risk, but its significance was diminished by the addition of postnatal variables. Conclusion In this sample of extremely preterm born infants, antenatal as well as early and late postnatal characteristics and exposures are associated with an increased risk of having a VFD. Our study adds to our knowledge about the complex etiology of visual deficits of prematurity, and supports a multifactorial cause of these deficits.